The effectiveness of cognitive behavioral group therapy on anxiety-depressive symptoms and emotion regulation in child laborers - Salek Ebrahimi , Leila; Abasi, Imaneh; Ghasemzadeh, Sogand; Mohammadi, Abolfazl; Saberi Isfeedvajani, Mohsen; Masjedi Arani, Abbas (Researcher Bulletin of Medical Sciences, 2020)
Objectives: This study was aimed to determine the effectiveness of Cognitive Behavioral Group Therapy on anxiety-depressive symptoms and emotion regulation in child laborers. Materials & Methods: This study was a randomized clinical trial conducted on child laborers. The obtained data were collected from 15 participants in the experimental and 15 in the control group. The members of control group didn’t receive any intervention. The participants in experimental group received the cognitive-behavioral group therapy based on "coping cat" program. The treatment consisted of 18 weeks of 90-min sessions meeting once a week. Participants of two groups completed the Revised Child Anxiety and Depression Scale (R-CADS) and Cognitive Emotion Regulation Questionnaire-child version (CERQ-K) before and after intervention and three months later. Results: Repeated measurement of ANOVA indicated that the CBT significantly decreased depressive-anxiety symptoms and negative emotion regulation strategies as well as increased positive emotion regulation strategies. Furthermore, results yielded moderate to large effect sizes for improvement of dependent variables. Conclusion: This study showed significant differences in anxiety-depressive symptoms and emotion regulation between two groups. Therefore, CBT seems to be an effective intervention in child laborers. However when applying this intervention, the special cultural, social, educational and economic conditions of these children must be considered.